Identification of IL-10 Gene Polymorphisms in Leprosy - Desi Oktariana; Susilawati Susilawati; Gita Dwi Prasasti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
Background: Leprosy is a chronic disease caused by an infection of Mycobacterium leprae, which affects skin and nerve lesions, which can result in disability. The prevalence of leprosy continues to increase, especially in Indonesia, which is one of the endemic areas of leprosy. The unique immune response of each individual not only determines the susceptibility of individuals to leprosy, but also determines the type of leprosy that will manifest. One of the immune responses that plays an important role in the pathogenesis of leprosy is interleukin-10 (IL-10). Increased regulation of IL-10 can have an effect on decreasing macrophage activity in killing bacteria. Production of IL-10 is regulated by genes that encode the cytokine. Gen IL-10 is located on chromosome 1q32. Polymorphism in this gene can cause variations in the function of IL-10 protein, which can then influence the process of microbial elimination in the development of leprosy.Objective: This study aimed to identify IL-10 -819 C / T gene polymorphisms which were cut with the MslI enzyme in lepers.Method: This study is a laboratory study, which is also an observational descriptive study with a cross sectional study approach to 40 subjects with leprosy. Identification of IL-10 -819 C / T gene polymorphism was carried out by PCR amplification and RFLP (restriction fragment length polymorphism) technique using the MslI enzyme. Results: Distribution of TT, CT, and CC genotypes in the study subjects were 0 (0%), 14 (35%), and 26 (65%). Based on age, the distribution was 0 (0%), 6 (15%), 19 (47.5%) for those under 50 years old, and 0 (0%), 8 (20%), 7 (17.5 %) for those over 50 years old. Based on gender, the distribution is 0 (0%), 5 (12.5%), 16 (40%) in men, and 0 (0%), 9 (22.5%), 10 (25%) in women. Based on the classification of diseases, the distribution was 0 (0%), 3 (7.5%), 7 (17.5%) for papalacillary, and 0 (0%), 11 (27.5%), 19 (47.5 %) for multibasilers. Conclusion: More wild type genotypes are found in lepers (65%). Keywords: leprosy, polymorphism, IL-10 gene